Induction of broad multifunctional CD8+ and CD4+ T cells by hepatitis B virus antigen-based synthetic long peptides ex vivo - Jansen, Diahann T. S. L.; de Beijer, Monique T. A.; Luijten, Robbie J.; Kwappenberg, Kitty; Wiekmeijer, Anna-Sophia; Kessler, Amy L.; Pieterman, Roel F. A.; Bouzid, Rachid; Krebber, Willem-Jan; de Man, Robert A.; Melief, Cornelis J. M.; Buschow, Sonja I. (Frontiers in Immunology, 2023)
Introduction Therapeutic vaccination based on synthetic long peptides (SLP®) containing both CD4+ and CD8+ T cell epitopes is a promising treatment strategy for chronic hepatitis B infection (cHBV). Methods We designed SLPs for three HBV proteins, HBcAg and the non-secreted proteins polymerase and X, and investigated their ability to induce T cell responses ex vivo. A set of 17 SLPs was constructed based on viral protein conservation, functionality, predicted and validated binders for prevalent human leukocyte antigen (HLA) supertypes, validated HLA I epitopes, and chemical producibility. Results All 17 SLPs were capable of inducing interferon gamma (IFNɣ) production in samples from four or more donors that had resolved an HBV infection in the past (resolver). Further analysis of the best performing SLPs demonstrated activation of both CD8+ and CD4+ multi-functional T cells in one or more resolver and patient sample(s). When investigating which SLP could activate HBV-specific T cells, the responses could be traced back to different peptides for each patient or resolver. Discussion This indicates that a large population of subjects with different HLA types can be covered by selecting a suitable mix of SLPs for therapeutic vaccine design. In conclusion, we designed a set of SLPs capable of inducing multifunctional CD8+ and CD4+ T cells ex vivo that create important components for a novel therapeutic vaccine to cure cHBV.